Defending State-Feedback Based Controllers Against Sensor Attacks - Luis Francisco Cómbita; Nicanor Quijano; Alvaro Cárdenas (Ingeniería, 2023)
Context: This paper is motivated by the need to improve the resilience of industrial control systems. Many control systems currently operating in the industry were designed and implemented before the boom in communications (wired and wireless networks) within industrial control systems. However, nowadays they operate connected to the communications network. This increase in connectivity has made the systems susceptible to cyber-attacks that seek to degrade the proper operation of the control loop even affecting only one sensor.